Ludwig Müller – nazismens chefteolog - Friis, Martin (Dansk Teologisk Tidsskrift, 2012)
This article attempts to cast light upon Ludwig Müller’s authorship. Müller was one of the leading figures in the German Christian (“DC”) Faith Movement during the 1930s. He was elected as the first (and only) Reichsbischof of the short-lived Protestant Reichskirche in the first half of the 1930s. For this reason his authorship presents unique insights into the DC-movement’s own reasoning concerning its particular view of the Evangelical-Protestant doctrine shared by many German theologians at that time. The article asserts that Müller’s theological reasoning – in his attempt to bring about a harmonization of EvangelicalProtestant doctrine and National-Socialist Weltanschauung – results in a perversion of the above-mentioned Christian doctrine due to a conspicuously anti-dogmatic (i.e. not-sin-oriented), a highly pragmatic oriented attitude towards Christian morals, and a one-sided focus on God’s immanence.